DECENTRALIZED THERMOPHILIC BIOHYDROGEN: A MORE EFFICIENT AND COST EFFECTIVE PROCESS - Rajesh K. Sani; Rajesh V. Shende; Sudhir Kumar; Aditya Bhalla (BioResources, 2011)
Nonfood lignocellulosic biomass is an ideal substrate for biohydrogen production. By avoiding pretreatment steps (acid, alkali, or enzymatic), there is potential to make the process economical. Utilization of regional untreated lignocellulosic biomass by cellulolytic and fermentative thermophiles in a consolidated mode using a single reactor is one of the ways to achieve economical and sustainable biohydrogen production. Employing these potential microorganisms along with decentralized biohydrogen energy production will lead us towards regional and national independence having a positive influence on the bioenergy sector.